A Middleware Framework between Mobility and IoT Using IEEE 802.15.4e Sensor Networks - Tanweer Alam (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2019)
In this paper, we propose a mobility framework for connecting the physical things in wireless ad hoc sensor networks. Our area of study is the internet of things by using an ad hoc sensor network. Our purpose in this study is to create a mobility framework for the internet of things. For example- how we connect many physical objects and give them a sense of sensing each other in an ad hoc environment. We can connect different physical objects in a framework of an ad hoc sensor network. Our main contribution is a new methodology for simulating mobility physical objects for the internet of things. Our methodology uses the correct and efficient simulation of the desired study and can be implemented in a framework of ad hoc sensor networks. Our study will generate a new framework for solving the issue of connectivity among physical objects. The proposed mobility framework is feasible to run among physical objects using the ad hoc sensor network.